Synthesis, Post-Modification and Fluorescence Properties of Boron Diketonate Complexes - Guieu, Samuel
A family of fluorescent dyes based on a boron diketonate core with extended conjugation has been prepared by a three-step strategy. The complexes are fluorescent both in solution and in the solid state, with a large Stokes' shift. A free phenol group can be used to further modify the compounds with no loss of emission efficiency.